Lectotypification of names of Quercus spp. (Fagaceae) described by Lamarck from the Iberian Peninsula - Vázquez, Francisco María; Coombes, Allen; Almeida, Rubim; Garcia-Alonso, David; Márquez-García, Francisco; Vila-Viçosa, Carlos (Phytotaxa, 2020)
The nomenclature of some species of Quercus described by Lamarck from the Iberian Peninsula is reviewed. Five names are lectotypified and two epitype are designated.